Season of birth as a risk factor for multiple sclerosis in Brazil - Becker, Jefferson; Callegaro, Dagoberto; Lana-Peixoto, Marco Aurélio; Ferreira, Maria Lúcia B.; Melo, Ailton; Diniz Da Gama, Paulo; Souza, Doralina G.B. [UNESP]; Teixeira, Carlos A.C.; Kaimen-Maciel, Damacio Ramón; Gonçalves, Marcus Vinícius; Matta, André P.C.; Abraham, Ronaldo; et al. (Elsevier, 2013)
Risk factors for development of multiple sclerosis (MS) are still a matter of debate. Latitude gradient, vitamin D deficiency and season of birth are among the most investigated environmental factors associated with the disease. Several international studies suggest that birth in spring is a substantial risk factor for MS. We investigated the season of birth as a potential risk for MS in different geographical regions of Brazil. We conducted a cross-sectional retrospective study with 2257 clinically definite MS patients enrolled in 13 Brazilian MS clinics in the south, southeast, and northeast regions of Brazil. Demographic and clinical data relating to date of birth and clinical features of the disease were collected and analysed, and subsequently compared with birth date among the general Brazilian population. The distribution of date of birth of MS patients showed an increase in spring and a decrease in autumn, with no difference being observed in the other seasons. In conclusion, season of birth is a probable risk factor for MS in most parts of Brazil. These findings may be related to the role that vitamin D plays in MS pathogenesis. © 2013 Elsevier B.V. All rights reserved.
Keywords: Month of birth; MS epidemiology; Multiple sclerosis; Risk factor; Season of birth; Vitamin D; adult; autumn; birth rate; Brazil; cross-sectional study; environmental factor; female; high temperature; human; major clinical study; male; multiple sclerosis; priority journal; risk assessment; risk factor; season of birth; spring